Inclusion of 2D Transition Metal Dichalcogenides in Perovskite Inks and Their Influence on Solar Cell Performance - Nicola Taurisano; Gianluca Bravetti; Sonia Carallo; Meiying Liang; Oskar Ronan; Dahnan Spurling; João Coelho; Valeria Nicolosi; Silvia Colella; Giuseppe Gigli; Andrea Listorti; Aurora Rizzo (Nanomaterials, 2021)
Organic–inorganic hybrid perovskite materials have raised great interest in recent years due to their excellent optoelectronic properties, which promise stunning improvements in photovoltaic technologies. Moreover, two-dimensional layered materials such as graphene, its derivatives, and transition metal dichalcogenides have been extensively investigated for a wide range of electronic and optoelectronic applications and have recently shown a synergistic effect in combination with hybrid perovskite materials. Here, we report on the inclusion of liquid-phase exfoliated molybdenum disulfide nanosheets into different perovskite precursor solutions, exploring their influence on final device performance. We compared the effect of such additives upon the growth of diverse perovskites, namely CH3NH3PbI3 (MAPbI3) and triple-cation with mixed halides Csx (MA0.17FA0.83)(1−x)Pb (I0.83Br0.17)3 perovskite. We show how for the referential MAPbI3 materials the addition of the MoS2 additive leads to the formation of larger, highly crystalline grains, which result in a remarkable 15% relative improvement in power conversion efficiency. On the other hand, for the mixed cation–halide perovskite no improvements were observed, confirming that the nucleation process for the two materials is differently influenced by the presence of MoS2.